Transnational Modern Languages A Handbook - Burns, Jennifer; Duncan, Derek (Liverpool University Press, 2022)
In a world increasingly defined by the transnational and translingual, and by the pressures of globalization, it has become difficult to study culture as primarily a national phenomenon. A Handbook offers students across Modern Languages an introduction to the kind of methodological questions they need to look at culture transnationally. Each of the short essays takes a key concept in cultural study and suggests how it might be used to explore and illuminate some aspect of identity, mobility, translation, and cultural exchange across borders. The authors range over different language areas and their wide chronological reach provides broad coverage, as well as a flexible and practical methodology for studying cultures in a transnational framework. The essays show that an inclusive, transnational vision and practice of Modern Languages is central to understanding human interaction in an inclusive, globalized society. A Handbook stands as an effective and necessary theoretical and thematically diverse glossary and companion to the 'national' volumes in the series.